1994
DOI: 10.1203/00006450-199404000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and Fetal Intervention Interact to Alter Lung Maturation in Preterm Lambs

Abstract: MATERIALS AND METHODSincrease lung volumes, and decrease epithelial and endothelial permeability without increasing alveolar surfactant pool sizes in ventilated preterm rabbits and sheep (4,5). Prenatal corticosteroid exposure also can alter neuroendocrine adaptation and increase blood pressure and cardiac performance in the preterm resulting indirectly in improvements in pulmonary performance (6). Despite these many observations. inconsistent responses to prenatal corticosteroid exposure continue to be report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…In studies using human fetal lung explant, glucocortic oids have both a stimulatory and an inhibitory effect on the SP-A synthesis: low doses and short exposure stimulate, whereas high doses and long exposure inhibit the synthesis of SP-A (7). Furthermore, prenatal glucocorticoid treatment increases the expression of SP-A in the whole lung of the rat fetus (26), and prenatal glucocorticoid treatment combined with TSH-releasing hormone or fetal intervention s increases the alveolar pool size of SP-A in ventilated preterm sheep (12,27). In the present study, prenatal glucocorticoid administration tended to increase the ratio between SP-A and PC on the first day of life.…”
Section: Ta Ble 5 Minimum Surface Tension Of Surfactant Complex Isolmentioning
confidence: 48%
“…In studies using human fetal lung explant, glucocortic oids have both a stimulatory and an inhibitory effect on the SP-A synthesis: low doses and short exposure stimulate, whereas high doses and long exposure inhibit the synthesis of SP-A (7). Furthermore, prenatal glucocorticoid treatment increases the expression of SP-A in the whole lung of the rat fetus (26), and prenatal glucocorticoid treatment combined with TSH-releasing hormone or fetal intervention s increases the alveolar pool size of SP-A in ventilated preterm sheep (12,27). In the present study, prenatal glucocorticoid administration tended to increase the ratio between SP-A and PC on the first day of life.…”
Section: Ta Ble 5 Minimum Surface Tension Of Surfactant Complex Isolmentioning
confidence: 48%
“…29 Antenatal dexamethasone treatment of the ewes resulted in 2.2% to 6.8% reductions in regional brain water content at 60% of gestation ( Figure 3) compared with maturational changes in regional brain water content, which ranged from 20% to 46% (Figure 1). 19 Treatment of the ewes with corticosteroids did not have major effects on the brain or plasma electrolyte homeostasis of the fetuses. Moreover, catheterization of the fetus was also associated with 3.5-7.4% reductions in regional brain water content at 60% of gestation ( Table 3), suggesting that the stress of fetal surgery at this age also results in decreases in regional brain water that are as large as those observed after than matemal antenatal corticosteroid treatment.…”
Section: Discussionmentioning
confidence: 90%
“…1 5 Previous studies have shown that the response of the fetal lung to a maturational agent such as cortisol depends on the history of previous fetal interventions. 19 When a twin pregnancy was present, we initially obtained tissue samples from both the catheterized and noncatheterized fetuses. However, because catheterization represents a major fetal stressor, we analyzed the effects of catheterization on regional fetal water content and found that it was lower in the catheterized than the noncatheterized fetuses of the placebo-treated ewes (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…That we did not expose control animals to a sham amniocentesis 48 h before delivery also leaves open the possibility that procedure-related stress may have contributed in a beneficial way to those infants who subsequently cleared the Ureaplasma from their airways (53).…”
mentioning
confidence: 99%